The Influence of Pain on Masseter Spindle Afferent Discharge - Capra, Norman F. (2006)
Muscle spindles provide proprioceptive feedback supporting normal patterns of motor activity and kinesthetic sensibility. During mastication, jaw muscle spindles play an important role in monitoring and regulating the chewing cycle and the bite forces generated during mastication. Both acute and chronic orofacial pain disorders are associated with changes in proprioceptive feedback and motor function. Experimental jaw muscle pain also alters the normal response of masseter spindle afferents to ramp and hold jaw movements [1]. It has been proposed that altered motor function and proprioceptive input results from group III muscle afferent modulation of the fusimotor system which alters spindle afferent sensitivity in limb muscles[2]. The response to nociceptive stimuli may enhance or reduce the response of spindle afferents to proprioceptive stimuli. Several experimental observations suggesting the possibility that a similar mechanism also functions in jaw muscles are presented in this report. First, evidence is provided to show that nociceptive stimulation of the masseter muscle primarily influences the amplitude sensitivity of spindle afferents with relatively little effect on the dynamic sensitivity [3]. Second, reversible inactivation of the caudal trigeminal nuclei attenuates the nociceptive modulation of spindle afferents. Finally, functionally identified gamma-motoneurons in the trigeminal motor nucleus are modulated by intramuscular injection with algesic substances. Taken together, these results suggest that pain-induced modulation of spindle afferent responses are mediated by small diameter muscle afferents and that this modulation is dependent, in part, on the relay of muscle nociceptive information from trigeminal subnucleus caudalis onto trigeminal gamma-motoneurons. The implication of these results will be considered in light of current theories on the relationship between jaw muscle pain and oral motor function.